2016
DOI: 10.1371/journal.pone.0153362
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Number of Medical Malpractice Claims and Their Amounts

Abstract: Starting from an extensive database, pooling 9 years of data from the top three insurance brokers in Italy, and containing 38125 reported claims due to alleged cases of medical malpractice, we use an inhomogeneous Poisson process to model the number of medical malpractice claims in Italy. The intensity of the process is allowed to vary over time, and it depends on a set of covariates, like the size of the hospital, the medical department and the complexity of the medical operations performed. We choose the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 28 publications
0
19
2
4
Order By: Relevance
“…The data from malpractice claims is conflicting, as some studies show an increasing amount of malpractice claims, while in others there is a clear decrease. [34,35] In contrast to our results, the law appeared to play a limited role in end-of-life medical decision-making with doctors prioritizing patient-related clinical and ethical considerations in a recent study from Australia. [36] On the other hand, that study is partly in line with our study, as ethical values were also considered to be highly influential by our responders.…”
Section: Factors Associated With Physicians' Decisionscontrasting
confidence: 99%
“…The data from malpractice claims is conflicting, as some studies show an increasing amount of malpractice claims, while in others there is a clear decrease. [34,35] In contrast to our results, the law appeared to play a limited role in end-of-life medical decision-making with doctors prioritizing patient-related clinical and ethical considerations in a recent study from Australia. [36] On the other hand, that study is partly in line with our study, as ethical values were also considered to be highly influential by our responders.…”
Section: Factors Associated With Physicians' Decisionscontrasting
confidence: 99%
“…Naturally, this is primarily a function of frequency, since cases such as inguinal hernia repair or appendectomy are simply the most prevalent procedures. This has been described by others, and in other subspecialties as well [3,15,19]. A recent study that queried a national database on malpractice cases in the USA also found that technical complications were the most common allegation against surgeons, followed by cases that involved a delayed or missed diagnosis [20].…”
Section: Discussionmentioning
confidence: 54%
“…While, in Ukraine in general: obstetricians-gynecologists -33%; surgeons -20%; anesthesiologists -12%; ambulance workers -7.5%; paramedics -5%; medical assistants -5%, other specialties -17,5% (in total, one criminal case conducted in different specialties, except the above) of the total number of cases on which the convictions and acquittals were made between 2016 and 2019 and one case with information on which is confidential (Figure 2). Based on a study conducted by Marco Bonetti, Pasquale Cirillo, Paola Musile Tanzi, Elisabetta Trinchero in 15 regions of Italy from 2001 to 2012, the most frequently raised are claims of medical errors and medical professionals' negligence of such specialties as: surgery -20, 86%; orthopedics -11.08%; ambulance workers -10.88%; general medicine -10.11%; gynecology -6,72%; anesthesia -1.87%; other specializations -12,58%; not classified -14.32% and information on which is not available -11.58% of the total number of 38125 cases were initiated against medical professionals, which generally tells us that on average 3466 cases are initiated annually (Bonetti et al, 2016). Based on a study conducted by Burçin Gürbeden and Erdem Özkara in Turkey, it is possible to identify the most frequently prosecuted medical professions: 19.9% of emergency workers; obstetrics and gynecology -16%; anesthesiology -9,4%; surgery -8.3%; pediatrics -4.4% of the total number of 105 cases initiated in from 2010 to 2014 (Gürbeden and Özkara, 2018).…”
Section: Resultsmentioning
confidence: 99%